Surgical conscience and its role in patient safety and care - Farley, Margaret (Operating Room Nurses Association of Canada Journal, 2024)
Honesty and integrity in surgical practice environments is a cornerstone to infection prevention and control practices to assist in reducing the numbers of infections and providing optimal patient outcomes. The cost of ignoring a surgical conscience directly affects the patient. A surgical conscience is a vital necessary element of safe, ethical, competent surgical patient care, and is related to optimal patient outcomes, including the prevention of surgical site infections (SSI). It is often described as an inner “voice” reminding you of the correct thing to do in a surgical environment. This paper explores how surgical conscience is part of our practice and the role it plays in patient safety and best practices.